Toponymic names of hamlets in Sembalun District, East Lombok - Hariadi Hariadi; Saharudin Saharudin; Muh. Syahrul Qodri (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2023)
This research aims to describe the form and cultural meaning of the toponymic variants of naming hamlets in Sembalun District, East Lombok. The method used is a descriptive qualitative approach. The data in this research includes primary data obtained from books and official documents and secondary data in the form of information from sources who know the meaning of the names of hamlets in Sembalun. Then, the techniques used are library study techniques, interviews, recording and note taking. The analysis used is structural language analysis and anthropological linguistic analysis of the hamlet name terms used in naming hamlets in Sembalun District. The research results include three categories, namely word form, toponym variants, and the meaning of hope. First, form language units in the form of word compositions, with classification in the process of forming noun compositions with nouns, metaphorical noun compositions, noun compositions with adverbs, and noun compositions with adjectives. The composition of nouns with adverbs is the most dominant word composition unit found in the names of hamlets in Sembalun. Second, toponym variants are classified into embodiment aspects, social aspects and cultural aspects. Aspects of embodiment are found more at the level of the form of water, nature, and conditions of place (topography). Third, the meaning of naming hamlets in Sembalun District is classified based on the meaning of hope and the meaning of memory. The naming of hamlets in Sembalun District is more directed towards the hope that its people will have guidance in life, and be able to always surrender to their creator.